Shifting geographies of subversive politics in Istanbul - Gül, Zeynel. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This thesis aims to understand the shifts in the spaces of radical left politics and the effects of these shifts on the discourses and modalities of political actions in Istanbul since the mid-1990s. In order to achieve this aim, it draws on an analysis of spatial distribution of political actions in central city sites and urban margins. It also focuses on the temporal mapping of critical events that shape political processes. It demonstrates that there exists a mobility of concentration of the political actions from urban margins to central spaces in the city. Based on records of radical left publications and ethnographic research in the left-stronghold Gazi and Okmeydanı neighborhoods, the thesis argues that the radical left employs different idioms and space-making practices, which in turn shape the modalities of their political actions. On the one side, the violent sacrificial practices by radical left subjects vis-à-vis the state contribute to the making of subversive neighborhood spaces – via walls, corners, parks, squares, barricades. On the other side, the human rights discourse based on victimhood converges with the spatial vector oriented to spaces of visibility in city centers. In the spaces of visibility, the material, economic, sensual and bodily dimensions of political actions are erased; the violently targeted body of the political subject is reduced to spectacle and voice. The thesis proposes to add action and visibility to the set of defining characteristics of space-complex, which is mostly discussed along the axis of materiality, memory, belonging and narrativity.
Keywords: Community development -- Turkey.; Marginality, Social.